Trends in Prescriptions for Insomnia in a Province in China Between 2015 and 2019 - Lou, Guodong; Yu, Zhenwei; Chen, Liying; Zhou, Yiting; Zhang, Lisan (Frontiers in Psychiatry, 2022)
Background: The inappropriate use of pharmacological treatments for insomnia may increase patients’ risk of serious adverse events. However, few epidemiological studies on the use of medications for insomnia in China have been conducted to date. Objective: We aimed to investigate the current pharmacological treatments for insomnia and guide the rational use of drugs. Methods: The prescription data of outpatients with insomnia between 2015 and 2019 in Zhejiang province were extracted from the Hospital Prescription Analysis Cooperative Project of China and evaluated. The demographic characteristics of insomnia and the proportion and prescription trends of different drugs were analyzed along with multidrug combinations for insomnia. Results: The number of patients with insomnia who were prescribed medications for insomnia increased from 2,385 in 2015 to 3,919 in 2019, with an increase of 64.32%, whereas the mean age of these patients decreased from 64.07 years to 60.94 years. There were nearly 1.42 times as many female patients prescribed medications for insomnia as male patients, and female patients tended to be younger than male patients. Benzodiazepines (53.99%) were the most common type of medicine for insomnia. The incidence of benzodiazepine usage decreased signiﬁcantly yearly (P < 0.01), whereas the incidences of non-benzodiazepine receptor agonist (nBZRA) and antidepressant usage increased (P < 0.05). The most common benzodiazepine, nBZRA, antidepressant, and antipsychotic were estazolam, zolpidem, trazodone, and olanzapine, respectively. A total of 13.97% of outpatients with insomnia were prescribed multiple drugs for insomnia, even though nearly half of the drug combinations had similar pharmacological mechanisms. Conclusions: Benzodiazepines remained the most common medication for insomnia, but the prescription rates of nBZRAs and antidepressants increased. Attention should be paid to multidrug combinations for insomnia, which may lead to an increased risk of serious adverse effects.